Can Interest in Using Paylater Mediate Impulse Buying Behavior Online? - Amir Mahmud; Nuril Fatikhah (Dinamika Pendidikan, 2023)
This study aimed to analyze the effect of price rationality, sales promotion, and hedonic lifestyle on impulsive buying behaviour with an interest using paylater as a mediating variable. The research population is active students of the Faculty of Economics, Universitas Negeri Semarang class of 2019, totaling 974 students. The sampling technique used simple random sampling amounted to 284 students. Methods of data collection used a questionnaire and used descriptive analysis techniques and path analysis techniques with the Structural Equation Model by SmartPLS 3.0. The results of this study showed that all variables had a positive and significant effect on online impulsive buying behaviour. Interest using paylater is able to partial mediation the influence of price rationality, sales promotion, and hedonic lifestyle on online impulsive buying behaviour. Based on the conclusion above, researchers provide suggestions in the form of support so that in the future students are able to manage finances wisely, students continue to deepen their knowlegde of finance so students can sort out product that are really in a sales promotion in the sense that they are not tempted by marketing so they can adjust their needs.